Neuromuscular profiles of female collegiate athletes: variations in countermovement jump metrics across 8 NCAA Division I sports - Kraemer, W. J.; Vatne, E. A.; Saenz, C.; Jones, P. C.; Carpenter, T. J.; Cencer, D. A. Jr; Enchelmeyer, K. E.; Pulvermacher, K. R.; Quebedeaux, C. K.; Vatne, M. R.; Hagen, J. A. (The Journal of Strength and Conditioning Research, 2025)
This study investigated countermovement jump (CMJ) performance metrics among National Collegiate Athletic Association Division I female athletes in 8 sports. The purpose of this study was to assess sport-specific variations in CMJ metrics to inform targeted training. A total of 169 athletes from basketball, field hockey, gymnastics, ice hockey, lacrosse, soccer, swimming, and volleyball were included. Athletes completed 3 CMJ trials with metrics recorded from the best trial, including jump height, average and peak propulsive power, modified reactive strength index, relative peak braking power, and relative peak landing force. Data were analyzed using 1-way analysis of variance with significance at p = 0.05. Significant differences were observed across sports. Ice hockey athletes showed significantly higher jump height, peak propulsive power, and relative braking power compared with athletes in lacrosse, swimming, and field hockey. Findings suggest that athletes in explosive sports like ice hockey demonstrate superior CMJ performance, potentially due to high demands for rapid acceleration and deceleration in competition. These results can guide strength and conditioning coaches to tailor training programs to the specific neuromuscular demands of each sport, enhancing performance and reducing injury risks.